The contribution of a psychomotor stimulation to the process of independence for a visually impaired - Thaynara Rodrigues da Silva; Dênia Paula Gomes; Eveline Torres Pereira (Desafio Singular, 2013)
This study aimed at developing and implementing a program of psychomotor stimulation process-based orientation and mobility of the visually impaired, since this type of commitment has a direct influence on psychomotor development of the individual, affecting their autonomy and independence. The program was implemented in the Laboratory of Psychomotor Stimulation of the Federal University of Viçosa, with the theoretical basis of Psychomotricity. We chose the intrinsic case study, to observe and evaluate better the difficulties encountered by the technique of systematic observation and informal interviews with parents. One can perceive evolutions in visually handicapped studied in terms equilibrium, concept space and body schema, and also willing to perform activities of daily living, which interfere in their locomotion. We concluded that the process of orientation and mobility is paramount in the work of independence of the visually impaired, and that it is needed a psychomotor development stimulus since the beginning of his life, because the delays that may arise during their growth and maturation. It becomes important to apply qualitative approaches for further studies but with larger samples.